(untitled) (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2015)
The article describes the Hungarian databases that contain visual items from the area of Balkan folklore. These materials can be found in the archives of scientific research institutes, and contain Bulgarian, Greek, Croatian and Serbian folklore items, as well as items from other nations of the former Yugoslavia.